Knowledge and vaccination status on hepatitis B among the students of Patuakhali Science and Technology University, Bangladesh - Sabbir Ahmed, M.; Rahman, M. Wahidur; Fayeza, Fahmida; Sharmin, Tarana (International Journal Of Community Medicine And Public Health, 2018)
Background: Hepatitis B virus (HBV) infection is a serious global public health problem as well as in Bangladesh. The most common liver disease in Bangladesh is viral hepatitis. Bangladesh is an intermediate endemic zone for hepatitis B virus infection. Research shows that about 10 million people in Bangladesh have been suffering from hepatitis B. Methods: The research was a cross-sectional survey and appropriate statistical formula was used to select 341 respondents randomly. The data were collected through a pre-designed, pre-structured questionnaire, which was distributed among the students. All the data was analysed using Microsoft Excel 2013. Results: Most of the respondent 95% knew about hepatitis B and about 87% knew that it is a viral infection. About 69% students respond that hepatitis B can increase liver cancer. Among the respondents, 76% supported that hepatitis B can be transmitted by blood transfusion. Most of the students 82% supported blood transfusion as a causative factor and 67% informed that jaundice is the major sign and symptoms of hepatitis B. More than half of the students 53% reported that they were vaccinated for hepatitis B. The major reasons for not taking vaccination were lack of free time and lack of feeling of necessity for vaccination. Conclusions: The overall knowledge and vaccination status on hepatitis B virus was not satisfactory. Different types of seminars and campaigns on hepatitis B, arranged by university will help to increase the student’s level of knowledge on hepatitis B.